Four Scenarios of Arctic Futures in 2050 : Arctic Shipping Development and Arctic Maritime Governance in the Light of China’s Arctic Policy - Schuen, Claire (My University, 2021)
The Arctic is heated, both in the natural science and social science senses. Undeniably, ice melting in the Arctic is a matter of fact. More areas are emerging with shipping routes developing through high seas, which are remodelling maritime situation and impacting current maritime management mindsets. Arctic seems to become more accessible, regardless its harsh environmental limitations. There are increasing interests toward the Arctic around the world. China, with its 2018 white paper of Arctic policy, is one of those countries that are seeking to expand participation in Arctic activities. The changing Arctic region is embedded with uncertainties and affecting both geographically and societally the future. By studying the futures of the Arctic, we would be able to address this task from a macro perspective via scenario thinking and analysis in compact. The research design unwinds alternative futures of the Arctic on matter of Arctic shipping and maritime governance with Dator’s four generic futures. Through a futures table exercise, variables are extracted from policy documents and public release, a set of scenarios are constructed. They are: continued growth scenario, collapse scenario, disciplined society scenario and transformational scenario. Personas and storylines are applied to present research results with the parity to stress on the differences of each scenario for comparison purpose. Alternative futures of the Arctic are challenging to conceptualise nor be predicted, due to the vigorous attribute of change-occurring nature encapsulated with evolving uncertainties.

Arktinen alue on kuuma aihe sekä luonnontieteellisessä että yhteiskuntatieteellisessä mielessä. Jään sulaminen arktisella alueella on kiistämätön fakta. Lisää alueita avautuu, kun merireitit kehittyvät avomereksi, mikä uudistaa merenkulun tilannetta ja vaikuttaa olemassa olevaan merenkulun hallintaan. Arktinen alue näyttää olevan helpommin saavutettavissa ankarista ympäristöolosuhteistaan huolimatta. Kiinnostus arktista aluetta kohtaan kasvaa ympäri maailmaa. Kiina on vuoden 2018 arktisen politiikan strategiallaan yksi niistä maista, jotka pyrkivät lisäämään osallistumistaan arktiseen toimintaan. Arktisen alueen muutos sisältää epävarmuuksia, jotka vaikuttavat sekä maantieteelliseen että yhteiskunnalliseen tulevaisuuteen. Tutkimalla arktisen alueen tulevaisuutta voimme käsitellä tätä kysymystä makronäkymästä skenaarioajattelun ja morfologisen analyysin avulla. Tutkimus jäsentää arktisen alueen vaihtoehtoisia tulevaisuuksia arktisessa merenkulussa ja merenkulun hallinnassa käyttäen Datorin neljää geneeristä tulevaisuutta valittuina tulevaisuuden arkkityyppeinä. Muuttujat poimitaan poliittisista asiakirjoista ja muista julkaisuista ja tulevaisuustaulukon avulla rakennetaan vuodelle 2050 joukko skenaarioita, jotka ovat: jatkuvan kasvun skenaario, romahtamisskenaario, kurinalaisen yhteiskunnan skenaario ja muutosskenaario. Henkilöitä ja tapahtumia käytetään skenaarionarratiiveina tutkimustulosten esittämiseen korostamalla kunkin skenaarion eroja. Arktisen alueen vaihtoehtoiset tulevaisuudet ovat haastavia käsitteellistää tai ennustaa johtuen voimakkaista ympäristössä tapahtuvista muutoksista, joita ympäröivät lukuisat dynaamiset epävarmuustekijät.
Keywords: Arctic Futures, Arctic Shipping, Maritime Governance, China’s Arctic Policy, Scenario Thinking, Persona, Storyline, Scenario, Four Generic Futures, Futures Table, Arktiset skenaariot, Arktinen merenkulku, Merenkulun hallinta, Kiinan arktinen politiikka, Skenaarioajattelu, Tulevaisuusnarratiivi, Skenaarioarkkityypit, Tulevaisuustaulukko